2017
DOI: 10.1371/journal.pone.0180065
|View full text |Cite
|
Sign up to set email alerts
|

Double hit of NEMO gene in preeclampsia

Abstract: The precise etiology of preeclampsia is unknown. Family studies indicate that both genetic and environmental factors influence its development. One of these factors is NFkB, whose activation depends on NEMO (NFkB essential modulator. This is the first study to investigate the association between the existence of single nucleotide variant of the NEMO gene and the appearance of preeclampsia. A total of 151 women (72 preeclamptic women and 79 controls) and their children were examined. Sanger sequencing was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Schematic representation of relationship between preeclampsia, incontinentia pigmenti and NEMO/IKBKG gene. : * : This article; Ref …”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Schematic representation of relationship between preeclampsia, incontinentia pigmenti and NEMO/IKBKG gene. : * : This article; Ref …”
Section: Discussionmentioning
confidence: 97%
“…Multiple mechanisms of pathogenicity of PE have been proposed, nevertheless, the exaggeration of systemic inflammation and endothelial dysfunction are still considered to be the most possible mechanisms . Studies have shown that PE is associated with an improper immune response and milieu of alternatively activated immune cells and cytokines . Placental ischemia, resulting from the insufficient trophoblast invasion seen in PE, has been shown to produce an imbalance in immune function that leads to chronic inflammation and manifests similarly to an autoimmune disease .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations